Impact of US-China Trade War on Indian External Trade - Anirban Sanyal (ZBW - Leibniz Information Centre for Economics, 2021)
The recent US-China trade war refreshed the memory of trade protectionism in the era of global integration. In this context, this paper analyzes the impact of higher trade tariffs imposed by the US and China on each other, on India, a large country having significant trade ties with both the US and China, yet not directly involved in the tariff war. Using product level data on exports and imports, the paper analyzes the implication of the tariff war on India in short run through the lens of trade diversion and identifies the differential effect of trade diversion across different product types. The analysis reveals a significant trade diversion to India from China at an aggregate level with trade elasticity of 0.5-0.7 due to US tariffs on China which points towards a substitution effect in products targeted by the US-China tariffs. Further, the paper observes a heterogeneous impact of the trade diversion across different product classifications. Particularly, India's export of easily substituted products like final goods, homogeneous goods and high elastic goods, intensified plausibly driven by higher tariffs imposed by the US on China. However the effect on these tariffs on India's import intensity remains mixed.
Keywords: F1; F12; F13; F14; 330; US-China Trade War; Trade Cost; Product Heterogeneity; Comparative Advantages